Accident - Tsurumi, Andrea (Boston : Houghton Mifflin Harcourt, 2017)
When Lola accidentally knocks over a jug of juice all over her parent's favorite chair, her panic sets off a chain reaction that sends the whole town into chaos.
Keywords: Accidents -- Fiction; Fear -- Fiction; Forgiveness -- Fiction; Accidents -- Fiction; Fear -- Fiction; Forgiveness -- Fiction